Synthesis, Spectral Property and Dyeing Assessment of Azo Disperse Dyes Containing Carbonyl and Dicyanovinyl Groups - Choi, Yun Seok; Lee, Kun Su; Kim, Hye Jin; Choi, Jong Yun; Kang, Soon Bang; Lee, Eui Jae; Keum, Gyochang (WILEY-V C H VERLAG GMBH, 2013)
A series of azo disperse dyes having dicyanovinyl groups was synthesized by the Knoevenagel condensation with malononitrile from carbonyl substituted phenylazo disperse dyes which were prepared by conventional diazo coupling reaction of aniline derivatives as diazo components. A variety of coupling components such as anilines, an indole and a pyridone were used. The azo disperse dyes were evaluated for their spectral properties and dyeing assessment on the polyester fabrics. The azo disperse dyes containing dicyanovinyl groups showed bathochromic shifts and darker colors due to increased electron withdrawing strength in their azo components and extended conjugation by dicyanovinyl groups than their parent carbonyl substituted azo dyes. The dyes containing 2-acetylamino-5-methoxy substituent in the coupling component exhibited higher wavelength of maximum absorbance (lambda(max)) and significant negative solvatochromism than those of other dyes due to intramolecular hydrogen bonding.